The Impact of Halal Certificate Ownership on MSME Income in Indonesia - Novari, Eri; Asih, Vemy Suci; Yulandri, Elsa; Supratman, Iman; Gojali, Dudang (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The ownership of halal certification can raise the likelihood of increasing SMEs' well-being, especially through revenue enhancement, according to this research, which empirically investigates the elements thought to motivate SME actors to seek halal certification. To accomplish the predefined research goals, the researcher employed a questionnaire survey with SMEs in Indonesia to gather data. The sample was chosen using the Cluster Random Sampling approach, and structural equation modeling (SEM) was used for analysis. The findings show that halal certification ownership affects income improvement, while halal literacy and accessibility affect halal certification ownership. The findings demonstrate how halal knowledge and accessibility affect the ownership of halal certification and how this affects SMEs' well-being. The research findings have management effects, such as offering a model for halal certification ownership as a policy guideline and promoting Halal Go Digital to help SMEs digitize their operations and make use of helpful features. With the use of this research, the government may develop a halal supply chain that involves both public and commercial entities and is coordinated across sectors.